La regulación emocional como categoría transdiagnóstica a través de los problemas clínicos: un estudio narrativo - Paredes Rivera Alvaro (2021)
In the diagnostic process of psychological disorders, we can find common characteristics to different problems, being able to explain a variety of clinical difficulties and comorbidities from this cross-sectional category, which has been called transdiagnostic. Being emotional regulation a transdiagnostic variable that is defined as the ability of the person to make use of resources or skills to modulate the behavioral response produced after experiencing a moderate to high intensity emotion.